The Effect of Rating, Online Consumer Review and Sales Promotion on Purchase Intention on the Gofood Application - Gigieh Giri Putra Prianika; Eka Bertuah (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the effect of ratings, online consumer reviews and sales promotion on purchase intention. This research is causal research, using multiple linear regression analysis methods. The population in this study were people who had bought food through Go-food during the last 3 months in the Jabodetabek area. The sample in this study used purposive sampling method with a total of 200 respondents. The results of this study indicate that rating, online consumer review and sales promotion simultaneously affect purchase intention. Rating has no positive effect on purchase intention. Online consumer review has a positive effect on purchase intention. Sales promotion has a positive effect on purchase intention. Then rating is not a variable that has a dominant effect on purchase intention